Roses - Meacham, Leila 1938- (New York : Grand Central Pub., 2010)
Having not married in spite of their true feelings, cotton tycoon Mary Toliver and timber magnate Percy Warwick struggle with deceit, secrets, and tragedies that challenge their children and grandchildren in their small east Texas community.
Keywords: Cities and towns -- Fiction -- Texas; City and town life -- Fiction -- Texas; Lumber industry -- Fiction -- Texas; Cotton industry -- Fiction -- Texas